Impact of isotopic effect on density limit and LHCD efficiency in the FT-2 experiments. (19th June 2015) - Lashkul, S.I.; Altukhov, A.B.; Gurchenko, A.D.; Gusakov, E.Z.; Dyachenko, V.V.; Esipov, L.A.; Irzak, M.A.; Kantor, M.Yu.; Kouprienko, D.V.; Perevalov, A.A.; Saveliev, A.N.; Shatalin, S.V.; et al.
Abstract: Current drive by lower hybrid waves (LHCD) is the most effective method to sustain the plasma current, but it is feasible only at the plasma density not exceeding some density limit n DL . In the present work the main attention is paid to the investigation of this effect on the FT-2 ( R  = 0.55 m, a  = 0.08 m, B T  ⩽ 3 T, I pl  = 19–40 kA, f 0  = 920 MHz) tokamak. The dependence of LHCD efficiency on isotopic plasma content (hydrogen/deuterium) is studied. Characteristic features of such an experiment are a strong influence of the isotope plasma composition on the LH resonance density n LH . For hydrogen plasma n LH  ≈ 3.5 × 10 19  m −3, while for deuterium plasma n LH  ≈ 2 × 10 20  m −3 . The suppression of the LHCD and beginning of the interaction of LH waves with ions are determined by the hydrogen/deuterium plasma density rise. In the hot hydrogen plasma ( T e ( r  = 0 cm) ≈ 700 eV) the density limit n DL of LHCD is approximately equal to the resonance value n LH  ≈  n LC, where n LC is the point of linear conversion. In the hot deuterium plasma one could expect an increase of n DL because of a much higher value of n LH  ⩾  n LC  ≈ 10 20  m −3 . However it appeared that the observed density limit for LHCD generation n DL  ≈ (3.5–4) × 10 19  m −3 is not determined by n LH . The role of parametric instabilities in CD switch-off is considered in both cases. The cooling of the plasma column and density rise could lead to a reduction of the threshold for the parametric decay of f 0 and result in early suppression of LHCD. In both cases the LHCD was inversely proportional to the density, which corresponds to the theoretical predictions. In order to analyse the experimentally observed LHCD efficiency the GRILL3D and FRTC codes have been used.